Metode Dakwah pada Suku Anak Dalam (SAD) Jambi - M Hambali (Dakwah Institut PTIQ Jakarta, 2023)
The Indeginous tribe is a minority tribe in Jambi. They have animism and dynamism beliefs that are hereditary in herited. In its development the Indeginous tribe, they have left their and cestors’ beliefs and preferred to embrace Islam. The process of trasfering faith is obtained at the instigation of the preacher. The first question in this research is, how are the da’wah strategies by applying the principles of Islamic Communication, tablîgh, taghyîr, takwîn al-ummah/amar makruf nahi munkar, dan khairiyah al-ummah/akhlâq as an effort to spread the religion of Islam in the Indeginous tribe?. While the second question is, what are the obstacles of da’wah faced by preachers in spreding Islam in the Indeginous tribe? The main theory used in this research is the theory of Islamic communication by Andi Faisal Bakti (2010) and Edi Amin (2017). The theory says that da’wah is done by four stages, namely tablîgh, taghyîr, takwîn al-ummah/amar makruf nahi munkar, dan khairiyah al-ummah/akhlâq. While the supporting theory used is attribution theory by Fretz Heider (1958) to know the obstacles of da’wah, namely ecological, psychological, and semantic. The results of this research indicate that da’wah done in the Indeginous tribe were in accordance with the stages of the islamic communication theory. Da’wah was done with a long proccess so that it changed. The changes occurred at the encouragement of culture and religions. The changes contineles to achieve physical and non-physical development, the peak of the Indeginous tribe formed the communities which religions values were well guided in da’wah, there were several obstacles, both internally and externally. Internal obstacles were influenced by semantic factor, while external obstacles were influenced by ecological and psychological faktors. The colclusion is the proccess of da’wah in the Indeginous tribe were in accordance with the stages of the islamic communication theory. There was a change both physically and non-physically in the Indeginous tribe into a positive and constructive directions. The external obstacles were more dominant such as environmental ecological than psychological and semantic.